ADVANTAGES AND DISADVANTAGES OF SOCIOSCIENTIFIC ISSUE-BASED INSTRUCTION IN SCIENCE CLASSROOMS - Evren Yapıcıoğlu, Ayşegül (International Online Journal of Education and Teaching, 2018)
The social roles and responsibilities expected from citizens are increasing due to changing global living conditions. Science education is expected to prepare conscious and sensitive students. Because today’s students are the adults of the future. Precondition of this task is Teacher Education. In the past decade, one of the most important research field of science education is socioscientific issues. The purpose of this research is to explore advantages and disadvantages of socioscientific issue based instruction in science classroom according to prospective science teachers’ views. A qualitative single case study design has been utilized. Prospective science teachers’ diaries and focus group interviews were used as data collection tools. Dolphinariums, Kyoto Protocol, genetically modified organisms, recyclable black bags’ benefits and damages, genetic tests, alternative energy sources and organ donation are examples of socioscientific issues, which are taught through activities in special teaching course. Findings of the study show that the advantages of socioscientific issue based instruction in science classroom comprise of six sub themes that are upskilling, social awareness, development of thinking, meaningful learning, character and professional development, contribution to scientific literacy whereas disadvantages of this instruction process are challenges teachers and students, limitations of teaching and learning process in prospective science teachers’ perspectives.